2002
DOI: 10.1021/jm0105530
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Potent, Nonsteroidal, and Highly Selective Glucocorticoid Receptor Antagonists

Abstract: An approach to the computer-assisted, pharmacophore design of nonsteroidal templates for the glucocorticoid receptor (GR) that contained an element of pseudo-C2 symmetry was developed. The enatiomer of the initial design, 1Ra, and not the designed molecule, 1S, showed the desired ligand binding to the GR. The pseudo-C2 symmetry of the template allowed for rapid improvements in GR activity resulting in potent, selective, nonsteroidal GR antagonists, CP-394531 and CP-409069.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 64 publications
0
40
0
Order By: Relevance
“…Finally, the recent disclosure by other members of the pharmaceutical industry of functional and selective GRs (sGRMs) provides additional evidence that novel NSGCAs can be obtained [20][21][22]. Hence, the NSGCAs described here, should stimulate further efforts to explore the potential for NSGCAs to lower plasma glucose levels and protein catabolism in vivo.…”
Section: Significancementioning
confidence: 90%
“…Finally, the recent disclosure by other members of the pharmaceutical industry of functional and selective GRs (sGRMs) provides additional evidence that novel NSGCAs can be obtained [20][21][22]. Hence, the NSGCAs described here, should stimulate further efforts to explore the potential for NSGCAs to lower plasma glucose levels and protein catabolism in vivo.…”
Section: Significancementioning
confidence: 90%
“…However, due to its stimulatory effect on the HPA axis, crossover to PR, and long half life, chronic usage is limited [Bamberger and Chrousos, 1995]. Non-steroidal GR antagonists have been identified [Betageri et al, 2005;Miner et al, 2003;Morgan et al, 2002]. However, pharmacological studies in animal models or clinical settings are not reported.…”
Section: Gr Antagonistmentioning
confidence: 99%
“…A detailed pairwise comparison is presented for the progesterone and androgen receptor, whose binding sites are very similar. High selectivity for only one of the closely related androgen, progesterone, glucocorticoid or mineralocorticoid receptors is important in order to reduce side effects of drug candidates [23,24].…”
Section: Introductionmentioning
confidence: 99%